2009
DOI: 10.1111/j.1471-0528.2009.02351.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal birth after two caesarean sections (VBAC‐2)—a systematic review with meta‐analysis of success rate and adverse outcomes of VBAC‐2 versus VBAC‐1 and repeat (third) caesarean sections

Abstract: Background Trial of vaginal birth after Caesarean (VBAC) is considered acceptable after one caesarean section (CS), however, women wishing to have trial after two CS are generally not allowed or counselled appropriately of efficacy and complications.Objective To perform a systematic review of literature on success rate of vaginal birth after two caesarean sections (VBAC-2) and associated adverse maternal and fetal outcomes; and compare with commonly accepted VBAC-1 and the alternative option of repeat third CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
122
5
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(146 citation statements)
references
References 34 publications
10
122
5
9
Order By: Relevance
“…Most women with a history of C-section are able to have a vaginal delivery; therefore, 75 out of 100 women will have successful vaginal deliveries and 25 out of 100 will require repetitive C-sections (31). A meta-analysis reported the success rate of vaginal birth after one C-section as 76.5% and after two Csections as 71.1% (28). Based on available evidence, vaginal birth is a suitable option for many women with a history of C-section with low transverse incision which also has different benefits and risks for the mother and the fetus (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most women with a history of C-section are able to have a vaginal delivery; therefore, 75 out of 100 women will have successful vaginal deliveries and 25 out of 100 will require repetitive C-sections (31). A meta-analysis reported the success rate of vaginal birth after one C-section as 76.5% and after two Csections as 71.1% (28). Based on available evidence, vaginal birth is a suitable option for many women with a history of C-section with low transverse incision which also has different benefits and risks for the mother and the fetus (32).…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive elective C-section is one of the main causes of increase in C-sections associated with fetal distress, dystocia (difficult birth), and breech presentation (28). Vaginal birth after C-section was one of the practical solutions introduced in the 1990s by the American College of Obstetricians and Gynecologists (ACOG) in order to reduce maternal and fetal complications of repeated C-section (29).…”
Section: Discussionmentioning
confidence: 99%
“…8 A trial of labor is generally not offered after two caesarean section as multiple caesarean sections are associated with many complications like scar integrity and placental complication. 9 Vaginal birth after cesarean section (VBAC) is associated with short period of hospitalization, less blood loss and fewer transfusions, fewer infections, and fewer thromboembolic events than cesarean delivery. 7 Several reports have indicated that the absolute risk of uterine rupture, attributable to a trial of labor is about 1 per 1000.…”
Section: Discussionmentioning
confidence: 99%
“…Trial of labor after caesarean (TOLAC) is a reported method to avoid repeated elective CS delivery [25,26]. A systematic review showed that the success rate of TOLAC after one CS was 76.5% and after two CS deliveries was 71.7% [27]. Robust programs to promote TOLAC among medical practitioners and among Egyptian females are necessary to reduce number of unnecessary caesareans.…”
Section: Discussionmentioning
confidence: 99%